Structural model of quality of life in women with breast cancer based on type D personality with mediating role of therapeutic compliance - Mirzaian Gizehroud, Seyedeh Sara; Monirpour, Nader; Akbari, Mohammad Esmaeil; Zargham Hajabi, Majid (Applied Family Therapy Journal (AFTJ), 2022)
Aim: To investigate the structural model of quality of life in women with breast cancer based on type D personality with mediating the role of compliance. Method: In this applied study, descriptive information of women with breast cancer referred to Shohada Tajrish Hospital and Azar Clinic in Tehran Collected in 1399-1399. The sample size was determined to be 440 people. Data collection tools included demographic quality of life questionnaire (EORTC QLQ-BR23), personality type scale D and general and specific compliance questionnaire of chronic patients by Hayes et al. (1994). Results: The coefficient of variable trajectory of type D on the treatment adherence of women with breast cancer which is 0.694 and also the t-statistic is 7.121, the coefficient of trajectory of the disease on the quality of patients studied is 0.887 Also, a t-statistic of 9.283 and finally a variable coefficient of type D personality trait were observed on the quality of life of women with breast cancer (0.523) and also a t-statistic of 4.120, all of which had a significant effect. Conclusion: Type D personality has a significant effect on the quality of life of women with breast cancer through mediation of adherence therapy and reduces the quality of life.